Artocarpin‐enriched (Artocarpus altilis) Heartwood Extract Provides Protection Against UVB‐induced Mechanical Damage in Dermal Fibroblasts. (25th July 2017) - Tiraravesit, Narisara; Humbert, Philippe; Robin, Sophie; Tissot, Marion; Viennet, Céline; Viyoch, Jarupa
Abstract: This study aimed to evaluate the protective effect of artocarpin‐enriched ( Artocarpus altilis ) heartwood extract on the mechanical properties of UVB‐irradiated fibroblasts. Human skin fibroblasts were pretreated with 50 μg/mL −1 extract and later irradiated with UVB (200 mJ/cm −2 ). They were then cultured within three‐dimensional of free‐floating and tense collagen lattices. The pretreatment of fibroblasts with the extract prior to UVB radiation showed cells protection against UVB‐induced suppression of α ‐SMA expression, fibroblast migration and contraction. These results reveal that the extract prevents mechanical damages induced by UVB irradiation in fibroblast‐embedded collagen lattices, and therefore, has a potential as a natural photo‐protectant. Abstract : Ultraviolet B radiation has a negative effect on the mechanical properties of the dermis and on the activities of resident fibroblasts, including the disorganization and fragmentation of the dermal extracellular matrix (ECM). It induces alterations in cytoskeleton structure, motility and the contractile forces of the fibroblasts. The present study aimed to evaluate the protective effect of Artocarpus altilis heartwood extract on the mechanical properties of ultraviolet B‐irradiated fibroblasts. Human skin fibroblasts were pretreated with 50 μg mL −1 artocarpin‐enriched extract for 48 h and later irradiated with ultraviolet B at 200 mJ cm −2 . They were then cultured within three‐dimensional models of free‐floating and tense collagen lattices. We analyzed collagen matrix retraction, contractile activity, the alpha‐smooth muscle actin ( α ‐SMA) cytoskeleton and the alpha2 integrin ( α 2 integrin) membrane receptor organization and/or expression in dermal fibroblasts. The pretreatment of fibroblasts with the extract prior to ultraviolet B irradiation showed that the cells were protected against UVB‐induced suppression of α ‐SMA expression, fibroblast migration and contraction. These results revealed that the A. altilis heartwood extract prevents the mechanical damage induced by ultraviolet B irradiation in fibroblast‐embedded collagen lattices and therefore has a potential as a natural photoprotectant.